The wolf shall dwell with the lamb : a spirituality for leadership in a multicultural community - Law, Eric H. F (St. Louis, Mo. : Chalice Press, 1993)
"Uses a combination of theology and cultural anthropology to explore why people of certain cultures--most notably whites of Northern European origin--tend to dominate in multicultural situations, driving those of other races and ethnic groups to silent rage or outright rebellion"--From publisher's description
1. The "peaceable realm" as a vision of an ideal multicultural community -- 2. What makes a lamb different from a wolf? : understanding cultural differences in the perception of power -- 3. Differences in the perception of power and their consequences for leadership -- 4. What does the Bible say to the powerful and the powerless? -- 5. A fresh look at Pentecost as the beginning of a multicultural church community -- 6. Who has power and who doesn't? : power analysis, an essential skill for leadership in a multicultural community -- 7. The wolves lie down with the lambs : a case study -- 8. Living out the fullness of the gospel in the peaceable realm -- 9. Mutual invitation as mutual empowerment -- 10. Media as means of distributing power -- 11. Liturgy as spiritual discipline for leadership in a multicultural community
Includes bibliographical references
Keywords: Multiculturalism -- Religious aspects -- Christianity; Intercultural communication -- Religious aspects -- Christianity; Christianity and culture; Power (Christian theology); Peace -- Religious aspects -- Christianity; Power (Mechanics) -- Religious aspects -- Christianity; Power (Philosophy) -- Religious aspects -- Christianity; Power (Social sciences) -- Religious aspects -- Christianity; Power resources -- Religious aspects -- Christianity